William Sydney Craves And his role in leading the American campaign in Siberia in 1918 (Journal of Misan Researches, 2020)
The research touched on the life of Commander William Sidney Graves since his birth in 1865 and his father's care and study, and then his enrollment in the Academy of Cadet, which had a significant impact in the refinement of his personality, included in the ranks and served in several places, especially the Spanish-American War of 1898, and the elimination of rebellions in the Philippines in 1902 In 1918, he was assigned to lead the U.S. campaign in Siberia, which, for reasons related to his character, faced many obstacles, including the presence of Allied forces that tried to dismember Russia, notably the Japanese's support for Admiral Kolchak, who declared himself governor of Siberia, but Graves with his skill and a person. He was able to maintain the goals set for him by the U.S. presidency and prevent the Allies from occupying any part of Russia, until the end of the campaign in November 1918 .